Seagrasses - Orlando-Bonaca, Martina (Annales. Series historia naturalis, 2025)
Seagrasses are unique marine flowering plants that provide critical ecological services and can serve as valuable reservoirs of bioactive compounds with potential health benefits. This review explores the bioactive metabolites found in four seagrass species native to European marine waters: Cymodocea nodosa, Posidonia oceanica, Zostera marina, and Nanozostera noltei. These species exhibit diverse chemical properties, including antioxidants, antimicrobials, and anti-inflammatory agents, making them promising candidates for pharmaceutical, nutraceutical, and cosmetic applications. Despite their promising applications in biotechnology, their full potential remains underexplored due to research and technological limitations. Future studies should focus on optimizing extraction methods, exploring synergistic interactions, and ensuring sustainable utilization of these valuable marine resources.
Keywords: bioactive compounds; bioaktivne spojine; cosmetics; European marine waters; evropske morske vode; farmacevtika; human health applications; kozmetika; marine biology; morska biologija; morske trave; nutriceutics; nutricevtika; pharmaceutics; seagrasses; uporaba za zdravje ljudi